2013
DOI: 10.1212/wnl.0b013e31827debd6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of idiopathic intracranial hypertension with transverse sinus stenosis

Abstract: Objective: Transverse sinus stenosis (TSS) is common in idiopathic intracranial hypertension (IIH), but its effect on the course and outcome of IIH is unknown. We evaluated differences in TSS characteristics between patients with IIH with "good" vs "poor" clinical courses.Methods: All patients with IIH seen in our institution after September 2009 who underwent a high-quality standardized brain magnetic resonance venogram (MRV) were included. Patients were categorized as having a good or poor clinical course ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 35 publications
7
114
0
Order By: Relevance
“…In fact, clear data on this topic are not available as only recently some reports have focused on the evaluation of the possible correlations between some clinical and instrumental aspects in the follow up of IIH patients [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, clear data on this topic are not available as only recently some reports have focused on the evaluation of the possible correlations between some clinical and instrumental aspects in the follow up of IIH patients [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…The main neuroimaging findings that may accompany IIH are empty sella (70%), distention (45%), and tortuosity (40%) of the perioptic subarachnoid space, flattening of the posterior sclera (80%), protrusion of optic nerve papillae into vitreous, and transverse sinus stenosis (90%) (Figure 2, 3) (4,7,30,33,34). It should not be forgotten that these findings are not specific to IIH and other pathologies that may cause these findings must 45 be evaluated.…”
Section: Diagnostic Criteria and Differential Diagnosismentioning
confidence: 99%
“…Anatomic studies have shown that stenosis is due to trabeculae, septa or hypertrophic granulomas (38). The presence of transverse sinus stenosis following normalization of CSF pressure in patients with IIH (39), and the absence of correlation between visual field loss and the degree of stenosis (34) suggest that stenosis is a result rather than an etiologic factor.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…However there is current evidence that some patients with IIH have bilateral transverse sinus stenosis (BTSS). [70] The transverse sinuses are well-known to be asymmetric in most individuals and an unilateral hypoplastic transverse sinus is considered a "normal variant" without any reported changes of ICP. MRV with an auto-triggered elliptic centric-ordered sequence demonstrated variable degrees of cerebral venous stenosis in most of the IIH cases compared with normal controls.…”
Section: New Insights From Neuro-imaging and Bilateral Transverse Sinmentioning
confidence: 99%